Mobile Application (apps) For Assessment Of Adverse Drug Reactions (ADRS): Causality, Severity And Preventability Assessment - Mohd Dzulkhairi Mohd Rani (Universiti Sains Malaysia, 2024)
Malay J Pharm Sci, Vol. 13, No. 1 (2015): 55–95